SISTEM INFORMASI LES PRIVAT KOTA KEDIRI BERBASIS ANDROID - Fery Sofian Efendi (Jurnal Informatika dan Multimedia, 2018)
Demanding knowledge Made of things that must be and must be implemented for every human being. One example of the demand for science at official official institutions such as in school. Currently there is no science that exist in schools that can improve the quality of students. Some of the learners at school may not be full-fledged. Lessons are taught in schools. For the exams undertaken the learners need to learn by alternative methods outside the school such as learning to learn or private lessons. Not a few individuals who also provide ease in the form of private lessons, in addition to alternative side jobs to help and improve the potential participants better locked in understanding the lessons in school or to face the school exam. The methods used are methods that still use manual methods, and are not effective in finding target participants and also participants who will choose a location close to home. Therefore, this research has resulted in an information application that allows users to access services and services that exist among the participants of the personal service and the learners. For the development of personal information system applications in cities using android systems still need to improve the security system because the system used is still needed and still needed, but also need to develop some features such as giving the rating on tentor, learners comment feature on tentor and validity period for account tentor or want a date or application.